Market Power and Capital Constraints - Wittwer, Milena; Allen, Jason (American Economic Review, 2026)
We explore how traders’ equity capitalization influences asset prices in a framework that accounts for market power. In our model, traders with capital constraints engage in transactions in an imperfectly competitive market. We demonstrate that looser capital constraints elevate both asset prices and price impact, the latter diminishing market liquidity. Using Canadian Treasury auction data, we illustrate how to apply our model to quantify these effects. We estimate the shadow costs of capital constraints by leveraging a temporary policy exemption during 2020–2021. We show that while these constraints are only infrequently binding, their relative impact when activated can be sizable. (JEL E63, G12, G14, G23, G41, L13)